Synthesis, chemical and biological properties of the new mono- and bis-derivatives of imidazoles - E. V. Welchinska (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2014)
The aim of research. The problem of finding effective antitumour medical preparation with low toxicity is an important issue of medical and pharmaceutical chemistry. Knowledge of cancer cell features and its metabolism enables to predict the direction of chemical and biological research, to conduct a targeted synthesis of potential drugs, and to assess their applicability in oncological practice as antitumor agents. The purpose of work is to explain preformed heterocycles as purines, its synthesis and investigation of chemical and biological properties. After construction of the potential active structures we proposed the new method of original derivatives synthesis which are received on the base of imidazole, from one side, and fluorocontaining common anesthetic halothane (2-bromo-1,1,1-trifluoro-2-chloroethane) from other side. Molecular complex of more perspective biologically active bis-imidazole with antitumour bacterial lectine has been received. With the purpose to synthesize potential antitumour compounds on the base of halothane and imidazole, new convenient methods for the preparation of original heterocyclic derivatives of imidazole have been described. The structure and composition of synthesized compound has been confirmed by the methods of elemental analysis, IR- and NMRІН-spectra.